Tumefactive Multiple Sclerosis Variants: Report of Two Cases of Schilder and Balo Diseases - ASHRAFI, Mahmoud Reza; TAVASOLI, Alireza; ALIZADEH, Houman; ZARE NOGHABI, Javad; PARVANEH, Nima (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Ashrafi Mr, Tavasoli AR, Alizadeh H, Zare Noghabi J, Parvaneh N. Tumefactive Multiple Sclerosis Variants: Report of Two Cases of Schilder and Balo Diseases. Iran J Child Neurol. Spring 2017; 11(2):69-77. Abstract A tumefactive lesion of central nervous system (CNS) is defined as a mass-like lesion with a size greater than 2 cm in brain detected by magnetic resonance imaging (MRI). Neuroimaging may help to distinguish the nature of a tumefactive lesion and therefore, can prevent an unnecessary brain biopsy. Here we emphasized on determining the nature of a CNS tumefactive lesions with the help of MRI and more explanations about demyelinating lesions with focus on Schilder and Balo diseases as two multiple sclerosis variants. We have reported here two boys of 10 and 8 years of age respectively of multiple sclerosis (MS) variants who presented with acute neurologic complications to our hospital as one of the two referral children hospital in Tehran, Iran. Tumefactive demyelinating lesions can be considered a separate entity that itself can contain Schilder disease, Balo disease, some cases of acute disseminated encephalomyelitis (ADEM) or classic MS. MRI can help to establish a diagnosis of a tumefactive lesion and to differentiate among different underlying etiologies. References 1. Bastianello S, Pichiecchio A, Spadaro M, Bergamaschi R, Bramanti P, Colonnese C, et al. Atypical multiple sclerosis: MRI findings and differential diagnosis. Neurol Sci 2004;25(4):S356-60. 2. Hinnell CJ, Lu JQ, Rajapakse T, Mah JK. Acute tumefactive inflammatory demyelination in a child. Pediatr Neurol 2011 44:394-5. 3. Legido A, Tenembaum SN, Katsetos CD, Menkes JH. Autoimmune and postinfectious disease in: Menkes JS, Sarnat HB; Maraia, BL, editors. Child Neurology. 7th ed. Philadephia: Lippincott Williams &Wilkins; 2006.p.557- 634. 4. Bacigaluppi S, Polonara G, Zavanone ML, Campanella R, Branca V, Gaini SM, et al. Schilder’s disease: non-invasive diagnosis? A case report and review. Neurol Sci 2009 30:421-30. 5. Fitzgerald MJ, Coleman LT. Recurrent myelinoclastic diffuse sclerosis: a case report of a child with Schilder’s variant of multiple sclerosis. Pediatr Radiol 2000; 30:861Ni. 6. Iniguez C, Pascual LF, Ramon y Cajal S, Fayed N, Morales-Asin F. Transitional multiple sclerosis (Schilder’s disease): a case report. J Neurol 2000;247:974-6. 7. Kraus D, Konen O, Straussberg R. Schilder’s disease: non-invasive diagnosis and successful treatment with human immunoglobulins. Eur J Paediatr Neurol 2012;16:206-8. 8. Orrell RW. Grand rounds--Hammersmith Hospitals. Distinguishing acute disseminated encephalomyelitis from multiple sclerosis. BMJ 1996;28;313:802-4. 9. Xia L, Lin S, Wang ZC, Li SW, Xu L, Wu J, et al. Tumefactive demyelinating lesions: nine cases and a review of the literature. Neurosurg Rev 2009;32:171-9. 10. Yilmaz Y, Kocaman C, Karabagli H, Ozek M. Is the brain biopsy obligatory or not for the diagnosis of Schilder’s disease? Review of the literature. Childs Nerv Syst 2008; 24:3-6. 11. Nadkar MY, Deore RA, Singh R. Tumefactive demyelination. J Assoc Physicians India 2008;56:901-3. 12. Sinha MK, Garg RK, Bhatt ML, Chandra A. Tumefactive demyelinating lesion: experience with two unusual patients. J Postgrad Med 2010;56:146-9. 13. Kiriyama T, Kataoka H, Taoka T, Tonomura Y, Terashima M, Morikawa M, et al. Characteristic neuroimaging in patients with tumefactive demyelinating lesions exceeding 30 mm. J Neuroimaging 2011;21:e69-77. 14. McAdam LC, Blaser SI, Banwell BL. Pediatric tumefactive demyelination: case series and review of the literature. Pediatr Neurol. 2002;26:18-25. 15. Love S. Demyelinating diseases. J Clin Pathol 2006;59:1151-9. 16. Badar F, Azfar SF, Ahmad I, Kirmani S, Rashid M. Balo’s concentric sclerosis involving bilateral thalami. Neurol India 2011;59:597-600. 17. Li Y, Xie P, Fan X, Tang H. Balo’s concentric sclerosis presenting with benign clinical course and multiple sclerosis-like lesions on magnetic resonance images. Neurol India 2009;57:66-8. 18. Pearce JM. Balo’s encephalitis periaxialis concentrica. Eur Neurol 2007;57:59-61. 19. Fillipi MDS, N; Dousset, V; MacGowan, JC. MR imaging in white matter diseases of brain and spinal cord. 1st ed. Germany: Springer; 2005. 20. Hernandez-Clares R, Di Capua D, Bartolome M, de Las Heras V, Arroyo R. Balo’s concentric sclerosis. Neurologia 2011;26:125-7. 21. Donati PR, A. Pediatric neuroradiology- brain, head, neck and spine. 1st ed. Germany: Springer; 2005. 22. Chiang IC, Hsieh TJ, Chiu ML, Liu GC, Kuo YT, Lin WC. Distinction between pyogenic brain abscess and necrotic brain tumour using 3-tesla MR spectroscopy, diffusion and perfusion imaging. Br J Radiol 2009;82:813-20. 23. Cianfoni A, Niku S, Imbesi SG. Metabolite findings in tumefactive demyelinating lesions utilizing short echo time proton magnetic resonance spectroscopy. AJNR 2007;28:272-7. 24. Masu K1, Beppu T, Fujiwara S, Kizawa H, Kashimura H, Kurose A, et al. Proton magnetic resonance spectroscopy and diffusion-weighted imaging of tumefactive demyelinating plaque. Neurol Med Chir 2009;49:430-3. 25. Muccio CF, Di Blasi A, Esposito G, Brunese L, D’Arco F, Caranci F. Perfusion and spectroscopy magnetic resonance imaging in a case of lymphocytic vasculitis mimicking brain tumor. Pol J Radiol 2013;78:66-9. 26. Panchal NJ, Niku S, Imbesi SG. Lymphocytic vasculitis mimicking aggressive multifocal cerebral neoplasm: mr imaging and MR spectroscopic appearance. AJNR 2005;26:642-5. 27. Gavra M, Boviatsis E, Stavrinou LC, Sakas D. Pitfalls in the diagnosis of a tumefactive demyelinating lesion: A case report. J Med Case Rep 2011;7:217.